2006
DOI: 10.1007/s11581-006-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport and battery discharge characteristics of polymer electrolyte based on PEO complexed with NaFeF4 salt

Abstract: Ion-conducting solvent-free solid polymer electrolytes based on polyethylene oxide (PEO) complexed with sodium ferric tetrafluoride (NaFeF 4 ) were prepared using a solution casting technique. The complexation of the films was investigated through X-ray diffraction and Fourier transform infrared spectroscopic studies. Measurements of DC conductivity in the temperature range 300-370 K and the transference numbers were carried out to investigate the nature of charge transport in the polymer electrolyte system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…The activation energies were evaluated from the slopes of log(σT) vs 1,000/T plots in regions I and II and show a decrease with increasing PVAc concentration. Similar behavior has been reported by other workers [24][25][26].…”
Section: Electrical Conductivitysupporting
confidence: 92%
“…The activation energies were evaluated from the slopes of log(σT) vs 1,000/T plots in regions I and II and show a decrease with increasing PVAc concentration. Similar behavior has been reported by other workers [24][25][26].…”
Section: Electrical Conductivitysupporting
confidence: 92%
“…They observed that the intensity of XRD pattern of PVA decreases as the amorphous nature increases with the addition of water. No sharp peaks were observed for higher concentrations of NaI salt in the polymer, suggesting the dominant presence of amorphous phase [19]. This amorphous nature results in greater ionic diffusivity with high ionic conductivity, which can be obtained in amorphous polymers that have flexible backbone [20].…”
Section: Xrd Analysismentioning
confidence: 97%
“…FTIR spectra of pure doped PVC with that of the pure PVC. The strong broad absorption band appearing in the 2769 -3088 cm -1 region in pure PVC corresponds to symmetric and asymmetric C -H stretching modes of the CH 2 groups 34 . With increasing dopant concentration the width increases and intensity of these bands in PVC is found to decrease.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%